C.P. Pow: Our intersecting academic pathways and some of his lasting contributions. Issue 1 (5th December 2022) - Bunnell, Tim
Abstract : C.P. Pow became a significant part of my own academic journey from soon after I joined the National University of Singapore (NUS) in 1999. Our academic inspirations, interests and identities overlapped, and we had opportunities to co‐teach and co‐write. I use these overlaps and collaborations as a way into reflecting on Pow's work, mainly during the period up to when he received tenure at NUS in 2011. I focus on two substantive themes. The first has to do with how and why Pow approached the landscape of Singapore beyond the visual or the 'seen'. The second theme concerns the origins, development and consolidation of Pow's contributions to examining urban Asia in ways that unsettle Anglo‐American‐derived generalizations.